Pemerintah, Civil Society, dan Akomodasi Media dalam Polemik Pemindahan dan Pembentukan Ibu Kota Negara Baru - Zaenal Muttaqin; Fauziah Muslimah; Andi M. Faisal Bakti; Yusron Razak (Fidikom UIN Jakarta, 2023)
This article aims to examine the strategy of the Joko Widodo’s Government in the policy of moving and establishing a new National Capital (IKN), the responses shown by civil society, and the role of the media in bridging the government's political communications. Using a qualitative approach with descriptive data analysis, the article outlines how the three subjects, the government, civil society groups and the media, carry-out their roles regarding the IKN. Utilizing Media and Civil Society Theory, the research analysis is focused on IKN news content in selected mass media. In addition, the research analyzes this topic from the perspective of scientific integration of da'wa communication. Research results show that the Jokowi’s government has built political communication by expanding coalitions in parliament as well as using internal media as an effective strategy in gaining support for the policy of moving and opening IKN. The article also notesthat the voice of the Civil Society group, which considered that the transfer of the IKN did not have social and political urgency, was not adequately accommodated. Finally, the research finds the vulnerability of media independence referring to accommodative tendencies of the media in reporting information on the birth of transfer policies and the establishment of the new capital.